Kondisi Hygiene dan Sanitasi Pedagang Sate Ayam di Kecamatan Kota Kabupaten Ngawi - Sunaryo Sunaryo (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
Based on the observations it was found that the quality of chicken satay exceeds the maximum limit of microbial contamination in food according to the quality standard of the Decree of the Head of the POM RI. So that researchers are interested in researching on the hygiene and sanitation of chicken satay traders in the City District, Ngawi Regency. This study aims to determine the condition of hygiene sanitation for chicken satay traders in the District of Kota Ngawi Regency in 2016. It is a descriptive study. The population of this study were all satay traders, with a large population of 21 traders. The sample of this research were all traders with a total population sampling technique, all of the population sampled is 21 traders. The research variable were the satay trade, from the characteristics of the selection of foodstuffs, storage of foodstuffs, and food processing. Collecting data by means of observation, and laboratory examinations of samples of material for making satay, in the Environmental Health Study Program of the Poltekkes Kemenkes Surabaya. Descriptive analysis of data in the form of frequency and percentage distribution, data presented in tables. The results showed that the assessment of the selection of foodstuffs obtained a sufficient category with a total score of 444 (70.47%), storage of foodstuffs obtained a good category with a total score of 528 (83.80%), food processing was obtained with a sufficient category with a total score of 1983 (69.94%), food transportation was obtained in a good category with a total score of 723 (76.50%), food presentation was obtained in a sufficient category with a total score of 450 (71.42%), and the number of germs was obtained in the less category with the number of 81 (42.85%). The conclusion from the sanitary condition of chicken satay traders is the selection of food ingredients, food processing, adequate food transportation, and adequate food presentation as well as a lack of germs.Keywords: chicken satay; hygiene; sanitation; street vendors ABSTRAK Berdasarkan hasil observasi ditemukan bahwa kualitas sate ayam melebihi batas maksimum cemaran mikroba dalam pangan sesuai dengan baku mutu Surat Keputusan Kepala Badan POM RI. Sehingga peneliti tertarik untuk meneliti tentang Hygiene Dan Sanitasi Pedagang Sate Ayam Di Kecamatan Kota Kabupaten Ngawi. Penelitian ini bertujuan untuk mengetahui kondisi hygiene sanitasi pedagang sate ayam di Kecamatan Kota Kabupaten Ngawi Tahun 2016. Merupakan penelitian deskriptif, populasi penelitian ini adalah seluruh pedagang Sate, besar populasi 21 pedagang. Sampel penelitian ini adalah seluruh pedagang dengan teknik sampling total populasi, semua pupulasi dijadikan sampel yaitu sebesar 21 pedagang. Variabel penelitian yaitu dagang sate, dari karakteristik pemilihan bahan makanan, penyimpanan bahan makanan, pengolahan makanan. Pengumpulan data dengan cara observasi, dan pemeriksaan laboratorium dari sampel bahan pembuatan sate, di Prodi Kesehatan Lingkungan Poltekkes Kemenkes Surabaya. Analisa data secara deskriptif berupa distribusi frekuensi dan presentase, data disajikan dalam bentuk table dan tekstuler.Hasil penelitian menunjukan penilaian pemilihan bahan makanan diperoleh kategori cukup dengan jumlah skor 444 (70,47%), penyimpanan bahan makanan diperoleh kategori baik dengan jumlah skor 528 (83,80%), pengolahan makanan diperoleh kategori cukup dengan jumlah skor 1983 (69,94%), pengangkutan makanan diperoleh dengan kategori baik dengan jumlah skor 723 (76,50%), penyajian makanan diperoleh dengan kategori cukup dengan jumlah skor 450 (71,42%), dan angka kuman diperoleh dengan kategori kurang dengan jumlah 81 (42,85%). Kesimpulan dari kondisi hygiene sanitasi pedagang sate ayam yaitu pemilihan bahan makanan, pengolahan makanan, pengangkutan makanan yang cukup, dan penyajian makanan yang cukup serta angka kuman yang masih kurang.Kata Kunci : sate ayam; hygiene; sanitasi; pedagang kaki lima